Strategi Pembelajaran Al-Quran Dengan Pendekatan Tahsin Dalam Memperbaiki Kualitas Bacaan Al-Quran Santri Di Sekolah Bumrungsuksa Islamic Boarding School (Bis) Hat Yai - Rizki, Muhammad; Zuliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine and describe Qur’anic learning strategies based on the tahsin approach in improving the quality of students’ Qur’an recitation at Bumrungsuksa Islamic Boarding School (BIS) Hat Yai, Thailand. The background of this research is rooted in the importance of accurate articulation of makharij al-huruf, mastery of letter characteristics, and correct application of tajwid rules in Qur’an recitation, particularly in Islamic boarding school–based educational institutions. Inaccuracies in these aspects may affect the quality of students’ recitation; therefore, structured, consistent, and continuous learning strategies are required. This research employed a qualitative approach with a descriptive design. Data were collected through participatory observation, in-depth interviews, and documentation during the implementation of the International Community Service Program (Kuliah Kerja Nyata Internasional / KKNI). The researcher was directly involved in tahsin learning activities, including student mentoring, observation of the learning process, and evaluation of Qur’an recitation. The findings indicate that tahsin learning at BIS Hat Yai is implemented intensively and continuously through the application of talaqqi, recitation submission, and habituation of Qur’an reading at specific times, such as after Subuh prayer, before Dhuhr, and before Maghrib. The learning process is further strengthened by intensive guidance provided by teachers and KKNI students. Supporting factors include a conducive boarding school system, consistent learning schedules, and high student motivation. Meanwhile, inhibiting factors consist of differences in students’ initial recitation abilities, limited number of tahsin teachers, and language barriers. Problem-solving efforts include grouping students based on their recitation proficiency, strengthening the role of learning companions, and adjusting learning methods. This study is expected to serve as a reference for the development of tahsin-based Qur’anic learning strategies in Islamic educational institutions.